1981-1982 ネン フジ コウロ ニ オケル クロロフィル α リョウ ブンプ ホウコク - 伊野, 良夫; イノ, ヨシオ; 福地, 光男; フクチ, ミツオ; Ino, Yoshio; Fukuchi, Mitsuo (1984)
P(論文) 1981-1982年, 第23次日本南極地域観測隊の海洋生物定常観測として, 「ふじ」船上で行われたクロロフィルa量の測定結果を報告する。 Data on chlorophyll a concentrations measured on board the FUJI as part of the marine biological programme of the 23rd Japanese Antarctic Research Expedition in 1981-1982 are presented. departmental bulletin paper